Modern ecological situation and nature management problems in Karachay-Cherkess republic - S. A. Khapaev; F. S. Khapaeva (Юг России: экология, развитие, 2015)
Ecological situations and the problems of natural management in Karachaevo-Cherkess republic are given in the light of the reorganizations of natural resources management.